Effect of acute exercise on vascular endothelial growth factor in adults: a systematic review with meta-analysis - Mohammad Javad Pourvaghar; Saeid reza Noorimofrad; Mousa Khalafi (فیزیولوژی ورزش و فعالیت بدنی, 2023)
Background and Purpose: Vascular endothelial growth factor (VEGF) is the most important marker of angiogenesis that may increase in response to exercise. However, the effect of acute exercise on this marker has been reported inconsistently. Therefore, the aim of this systematic review and meta-analysis is to investigate the effect of acute exercise on circulating VEGF in adults. Materials and Methods: In order to extract original articles, a comprehensive search was conducted in the databases of PubMed, Scopus, Web of Science, SID, Magiran and Google Scholar until 2023 March 1 for studies investigating the effects of acute exercise on circulating levels of VEGF. The meta-analysis criteria included studies published in Persian and English language journals, studies with human subjects with an average age of more than 18 years, studies investigating the effect of acute exercise, and studies measuring serum or plasma VEGF levels. To determine the effect size, standardized mean differences (SMD) values and 95% confidence intervals (CIs) were calculated using CMA2 software. The level of heterogeneity was assessed using the I2 test and the publication bias was also assessed with Egger's test.  Furthermore, subgroup analysis was performed for health status (with chronic disease and healthy) and type of exercise (aerobic, resistance and high-intensity interval exercise). Results: In total, 27 articles (49 exercise interventions) including 704 subjects were included in the meta-analysis. The results of data analysis showed that acute exercise did not lead to significant changes in VEGF immediately after exercise compared to baseline [0.17, (CI: -0.05 to 0.40, p=0.14). The results of subgroup analysis based on the health status showed that exercise had no significant effect on VEGF in healthy subjects [SMD: 0.10, p=0.40], while it tended to increase VEGF in patients [SMD: 0.30, p=0.05]. The results of the subgroup analysis based on the type of exercise also showed that resistance exercise [SMD: 0.58, p=0.008] leads to a significant increase and high-intensity interval exercise [SMD: 0.29, p=0.06] leads to a non-significant increase in VEGF, while the effect of aerobic exercise [SMD: 0.009, p=0.95] was not significant. Conclusion: In general, the findings of this meta-analysis showed that the type of exercise plays an effective role in the responses of VEGF to acute exercise. Resistance and high intensity interval exercise may lead to an increase in circulating VEGF immediately post exercise, while aerobic exercise does not have significant effects. In addition, exercise may increase VEGF in people with metabolic-cardiovascular disease, whereas, it is not effective in healthy individuals.